Bibliometric Analysis of Gene Research on Aging - Putri, Rachmagreta Perdana; Annisa, Annisa; Tejosukmono, Ario; Yuniasih, Dewi (Ahmad Dahlan Medical Journal, 2024)
Aging is associated with various factors identified in the hallmark of aging. Numerous studies have been conducted to identify genes involved in the aging process, allowing for a comprehensive understanding of this phenomenon. This study aims to provide an overview of research on genes associated with the aging process. Data for this study was obtained and analyzed from the SCOPUS database covering the period from 2014 to 2024, with a focus on medicine, neuroscience, and nursing. The keywords used for the search were "gene," "longevity," and "aging." The search results were filtered to match the study's purpose and were limited to articles in English. The data obtained was analyzed using VOSviewer version 1.6.20. A total of 1,603 articles were analyzed. The highest number of publications occurred in 2021. The most frequent sources for these articles were the journals Biogerontology and The Journals of Gerontology Series A: Biological Sciences and Medical Sciences. The United States was the leading contributor in publications (n=488), with Harvard Medical School producing the highest number (n=45). The most-cited article was by Loboda in 2016 (1,863 citations). Research on genes associated with aging has shifted from identifying genes (2017-2019) to focusing on the functions of these genes in physiological processes and other risk factors of aging. In conclusion, the aging research has evolved from focusing solely on gene identification to exploring the physiological functions and risk factors related to aging.